2018
DOI: 10.1371/journal.pone.0205836
|View full text |Cite
|
Sign up to set email alerts
|

Validation of deep-learning-based triage and acuity score using a large national dataset

Abstract: AimTriage is important in identifying high-risk patients amongst many less urgent patients as emergency department (ED) overcrowding has become a national crisis recently. This study aims to validate that a Deep-learning-based Triage and Acuity Score (DTAS) identifies high-risk patients more accurately than existing triage and acuity scores using a large national dataset.MethodsWe conducted a retrospective observational cohort study using data from the Korean National Emergency Department Information System (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 34 publications
0
80
0
Order By: Relevance
“…‡The alternative hypothesis for this p-value was that there is a difference between the ensemble model, combining artificial intelligence and the ESI, and the other predictive methods Meanwhile, deep learning includes feature learning, which allows the model to automatically learn the relationships and characteristics between input variables required to perform a task [30]. As shown in our previous studies, deep learning could be used to understand the connection between features and outperformed conventional and other machine learning methods [9,11,31]. It is important to note that feature learning is not designed by humans in deep learning.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…‡The alternative hypothesis for this p-value was that there is a difference between the ensemble model, combining artificial intelligence and the ESI, and the other predictive methods Meanwhile, deep learning includes feature learning, which allows the model to automatically learn the relationships and characteristics between input variables required to perform a task [30]. As shown in our previous studies, deep learning could be used to understand the connection between features and outperformed conventional and other machine learning methods [9,11,31]. It is important to note that feature learning is not designed by humans in deep learning.…”
Section: Discussionmentioning
confidence: 98%
“…Deep learning can obtain a high performance without prior knowledge to train the model; thus, indicating that deep learning somehow automatically learns the feature relationship among input variables. In our previous study, we developed an AI algorithm based on deep learning for predicting the critical care of patients in an ED [11]. From the previous study, we found that conventional statistical methods such as logistic regression may have difficulty in determining the relationship among input variables [10,28,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations